2014
DOI: 10.3390/ma7085438
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and Mechanical Performance of Carbon Fiber-Reinforced Polymer Used as the Impressed Current Anode Material

Abstract: An investigation was performed by using carbon fiber-reinforced polymer (CFRP) as the anode material in the impressed current cathodic protection (ICCP) system of steel reinforced concrete structures. The service life and performance of CFRP were investigated in simulated ICCP systems with various configurations. Constant current densities were maintained during the tests. No significant degradation in electrical and mechanical properties was found for CFRP subjected to anodic polarization with the selected ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…It was determined that an increasing applied current density leads to a decreasing tensile strength and elastic modulus in saturated Ca(OH)2 solution and in mix solution. [8] Similar experiments were conducted by Sun et. al.. [9] Uniaxial tensile tests on CFRP after polarization in simulated impressed current cathodic protection system with 3 % NaCl solution were carried out.…”
Section: State Of the Artsupporting
confidence: 66%
See 1 more Smart Citation
“…It was determined that an increasing applied current density leads to a decreasing tensile strength and elastic modulus in saturated Ca(OH)2 solution and in mix solution. [8] Similar experiments were conducted by Sun et. al.. [9] Uniaxial tensile tests on CFRP after polarization in simulated impressed current cathodic protection system with 3 % NaCl solution were carried out.…”
Section: State Of the Artsupporting
confidence: 66%
“…Mechanical performance of carbon fiber-reinforced polymer plates in simulated ICCP systems was investigated by Zhu et. al.. [8] The influence of different storage solutions and current densities on the mechanical properties of carbon fiber reinforced plates (CFRP) was tested. The examined CFRP plates were composed of multi-layer carbon fibers bounded by laminating epoxy.…”
Section: State Of the Artmentioning
confidence: 99%
“…Concrete and cementitious materials are vulnerable to tension developing in individual components and structures. Reinforcing materials such as steel fibers [ 1 , 2 , 3 , 4 , 5 , 6 ] are commonly used in concrete structures to control cracks [ 7 , 8 , 9 , 10 , 11 , 12 ]. The application of steel fiber reinforced shotcrete (SFRS) in tunneling construction has been part of tunneling practice since the 1970s, especially in Europe and the United States [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study [ 19 , 20 ], Zhu et al investigated CFRP’s mechanical and electrochemical performance during accelerated polarization in NaCl and NaOH solution environment. It was shown that CFRP can be successfully used as the anode in an ICCP system without significant degradation of mechanical properties in NaCl and NaOH solution environment [ 21 ]. Following these studies, this work presents a systematic investigation, including the electrochemical behavior, mechanical strength, and failure modes of CFRP during anodic polarization in a simulated pore solution environment.…”
Section: Introductionmentioning
confidence: 99%